THE EFFECTIVNESS OF TEAM BASED LEARNING IN READING ABILITY AT SMP MUHAMMADIYAH 6 MAKASSAR - Hafsa, Nur Afifa; Firman; Sastrawati, Ika (English Language Teaching Methodology, 2025)
The objective of the research was to find out the students’ reading ability  through Team Based Learning in Reading Ability  at SMP Muhammadiyah 6 Makassar.. This research used pre exprimental class with one class in pre-test and post-test. The population of the research was taken from the students at the eight  grade of SMP Muhammadiyah 10 Makassar. This population consisted of 120 students in consisted of fifth classes.The researcher used purposive sampling technique and  chose one class that consisted of  24 students as the sample.The results of the student's reading ability in mean score in pre-test (57,71) and in post-test (75.00). It had significantly different scores. The signicant score showed between pretest and posttest is 17 on the table show Sig. (2-tailed) is 000 lower then 0,005. It meant that there was a significant difference between the result the students’ pre-test and post-test. Therefore, hypothesis Ho was rejected and H1 was accepted.Based on the result above, it can be concluded that using Team Based Learning in Reading Ability  was effective in teaching reading ability at the eighth grade of at SMPN Muhammadiyah 6 Makassar.